Situation Report: Bulgaria, 10 July 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ailing First Deputy Prime Minister Released Private Services and Trade to Be Encouraged? New Bank to Promote Utilization of National Resources A New Corruption Scandal in Bulgarian Soccer